2021
DOI: 10.3892/ol.2021.12862
|View full text |Cite
|
Sign up to set email alerts
|

P4HA2 promotes cell proliferation and migration in glioblastoma

Abstract: Glioblastoma (GBM) is a primary malignant tumor characterized by high infiltration and angiogenesis in the brain parenchyma. Glioma stem cells (GSCs), a heterogeneous GBM cell type with the potential for self-renewal and differentiation to tumor cells, are responsible for the high malignancy of GBM. The purpose of the present study was to investigate the roles of significantly differentially expressed genes between GSCs and GBM cells in GBM progression. The gene profiles GSE74304 and GSE124145, containing 10 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…9 Consequently, collagen deposition interferes with cell polarity and adhesion, ultimately promoting cancer cell proliferation 34 and facilitating cancer cell invasion. 35 Previous studies found that P4HA2 was upregulated in GBM and promoted the proliferation, migration, and invasion of glioma cells, 36,37 consistent with our study. Unlike these previous studies, we found an unusual transcriptional expression pattern of P4HA2 that was at the lowest in LGG, in comparison to normal brain tissues and HGG.…”
Section: Discussionsupporting
confidence: 91%
“…9 Consequently, collagen deposition interferes with cell polarity and adhesion, ultimately promoting cancer cell proliferation 34 and facilitating cancer cell invasion. 35 Previous studies found that P4HA2 was upregulated in GBM and promoted the proliferation, migration, and invasion of glioma cells, 36,37 consistent with our study. Unlike these previous studies, we found an unusual transcriptional expression pattern of P4HA2 that was at the lowest in LGG, in comparison to normal brain tissues and HGG.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the PPI networks of the co-expressed genes suggested that collagen members, such as COL8A1, COL1A1, COL1A2, and the like, were the main connected components with COL5A1. Prolyl-4-hydroxylase subunit 2 (P4HA2), as one of the hub genes interacted the collagen members above, was reported to play an important role in tumor proliferation, migration, invasion, and epithelial-to-mesenchymal transition (EMT) in gliomas ( 32 , 33 ). Another similar hub gene Serpin family H member 1 (SERPINH1), also known as HSP47, was proved to promote GBM stem-like cell survival by modulating tumor microenvironment through TGF-β pathway ( 34 ) and enhance glioma angiogenesis through HIF1α-VEGFR2 signaling ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For primary hippocampal NSCs, the RNA was extracted 7 days after induced differentiation in DMEM/F-12 supplementing with 1% FBS and 100 U/mL penicillin-streptomycin 24 h after plasmid transfection or 48 h after lentivirus infection at 37°C with 5% CO 2 . As described previously [ 26 ], total RNA was extracted using Total RNA Isolation Reagent (Shanghai Pufei Biotechnology), cDNA synthesis was performed with a RevertAid First Strand cDNA Synthesis kit (Thermo Fisher Scientific), and RT-qPCR was performed with Universal SYBR Green Master Mix (Roche Diagnostics) according to the manufacturer's protocol using the following PCR conditions: 95°C for 10 min, followed by 40 cycles of 95°C for 30 s, 60°C for 30 s and 72°C for 40 s, followed by a final elongation step of 10 min at 72°C. Gene expression was normalized to β -actin expression calculated using the 2 −ΔΔCT method [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell Cycle Analysis. As described [26], NSCs were harvested 24 h after plasmid transfection or 48 h after lentivirus infection and then fixed with ice-cold 75% ethanol at -20 °C for at least 24 h. Next, cells were stained with Hoechst 33342 solution (BD Biosciences) and incubated for 30 min at RT, washed, and suspended in BD Pharmingen™ Stain Buffer (BD Biosciences). The results were analyzed using the BD FACSCalibur system (BD Biosciences) with ModFit LT v3.3.11 software (Verity Software House).…”
Section: Edu Incorporationmentioning
confidence: 99%